Características de carcaça e carne e concentração de cortisol sérico em bovinos de diferentes grupos genéticos - SANTOS, Aracele Pinheiro Pales dos (2010)
The aim of this study was to evaluate carcass characteristics, meat and quantify the concentrations of cortisol in animals of different genetic groups finished in feedlot.We evaluated 32 non-castrated male cattle from four different genetic groups, being: Nellore (N), Aberdeen Angus x Nelore (AN), Caracu x Nelore (CN), Guzerat x Nellore (GN). The AN group steers had average daily gain (1.28 kg ± 0.15), weight (from 50.61 ± 627.50 kg) and hot carcass weight (335.87 kg ± 31.48) than the others. The carcass yield was similar between the AN group (53.50 ± 1.30%) and group N (52.50% ± 1.06). Carcass conformation was similar between the AN group (12.12 ± 1.35) and the CN group (10.87 ± 0.83) and physiological maturity was similar between the genetic groups. The AN group showed genetic superiority (P <0.05) compared to others in most of the features that express the musculature of the carcass, being superior in at least 5.4% in carcass length and 6.7% in cushion thickness . In measuring the loin eye area of housing, the AN group (85.09 ± 11.4 cm2) was similar to the CN group (74.50 ± 7.82 cm2) and GN (73.93 ± 14.14 cm2).For fat thickness measured in the housing group AN (5.68 ± 1.16 mm) was higher than other groups. In the assessment of carcass physical composition, the groups were similar in the proportion of muscle (PMU), proportion of bone (POS) and edible portion (PCO), but the proportion of fat (PGO) was similar between the groups AN, GN and N, with a correlation between the PMU and PGO -0.92. The shear strength analysis showed no significant difference between the genetic groups. There was no difference in the thawing water loss and water loss during cooking. For the cortisol values were not significant differences between groups for the collection 1, 2 and 4, but in collecting and killing three group N and AN showed significant differences.